Pengaruh Pola Asuh Orang Tua Terhadap Motivasi Belajar Siswa Kelas V SD GMIM Desa Raanan Lama Kecamatan Motoling - Risal M. Merentek (Peneliti.net, 2021)
This study aims to determine whether there is an effect of parenting on the learning motivation of fourth grade students at GMIM Raanan Lama Elementary School. The type of research used is a quantitative approach with a survey method, where research is carried out using questionnaires as a research tool carried out on large and small populations, but the data studied are data from samples taken from the population, so that relative incidence, distributions are found. and the relationship between variables, sociological and psychological. Data collection is done by interview, quiz, observation, and a combination of the three. The instrument used is a questionnaire containing closed statements so that alternative respondents' answers have been provided by the researcher. Based on the t value, it is known that the tcount value is 5.860 > ttable 2.306 with a contribution of R 0.811 or 81.1%, which means that there is an effect of parenting patterns on the learning motivation of fourth grade elementary school students, with a magnitude of effect of 81.1% on motivation. student learning. Based on the results of the research and discussion, it can be concluded that there is a significant influence between parenting patterns on the learning motivation of fourth grade elementary school students.